The Comparative Study for Solving Fractional-Order Fornberg-Whitham Equation via ?-Laplace Transform - Sunthrayuth, Pongsakorn; Zidan, Ahmed M.; Yao, Shao-Wen; Shah, Rasool; İnç, Mustafa (Mdpi, 2021)
In this article, we also introduced two well-known computational techniques for solving the time-fractional Fornberg-Whitham equations. The methods suggested are the modified form of the variational iteration and Adomian decomposition techniques by rho-Laplace. Furthermore, an illustrative scheme is introduced to verify the accuracy of the available methods. The graphical representation of the exact and derived results is presented to show the suggested approaches reliability. The comparative solution analysis via graphs also represented the higher reliability and accuracy of the current techniques.
Keywords: rho-Laplace variational iteration method; rho-Laplace decomposition method; partial differential equation; caputo operator; fractional Fornberg-Whitham equation (FWE)